British tourists’ travel motivation, satisfaction and post travel behaviour towards visiting Malaysia / Noriman Rojulai - Rojulai, Noriman (2010)
Purpose of this study is to analyze the determinants of British tourist intentions to revisit Malaysia and also paying special attention to the effects of motivations and satisfaction. British tourists can be categorized as quality tourist and has enormous purchasing power when refers to their exchange rate. Satisfied British tourists may recommend Malaysia to others and may repeat their visit to Malaysia. Therefore, to understand their preferences is crucial in order to maintain existing tourist and attract new tourist from United Kingdom. Data was gathered by self-administered questionnaire at Kuala Lumpur International Airports (KLIA), Low Cost Carrier Terminal (LCCT) and Malaysia Tourism Centre (MTC). From the findings, the study revealed that there is a mix of pull and push factors. Top motivational factor was the push factor where the British tourists tend to experience different lifestyles and was followed by pull factors which are to enjoy the beautiful environment, scenery and beaches. The study also proofed that satisfaction mediate the relationship between motivation and post travel behaviour. The result obviously showed that satisfaction played the intervening role in influencing British Tourist to revisit Malaysia. The overall findings of this study provide valuable information and at the same time being an eye-opener for the government especially Ministry of Tourism and other related organization in providing and improving the products, facilities and services offered to the tourist especially British tourist.